2009
DOI: 10.1021/jp8111099
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation and Degradation of VX on Silica Sand

Abstract: The evaporation and degradation of VX (O-ethyl S-[2-N,N-(diisopropylamino)ethyl] methylphosphonothioate) on silica sand and borosilicate glass were measured using vapor analysis and 31 P solid state magic angle spinning nuclear magnetic resonance (SSMAS NMR) spectroscopy. 31 P SSMAS NMR studies of VX degradation on crushed glass, air-dried sand, and oven-dried sand at a variety of temperatures showed that the final product was nontoxic ethyl methylphosphonic acid (EMPA), produced via the toxic diethyl dimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 15 publications
3
38
0
Order By: Relevance
“…In such a situation, hydrolytic degradation, once initiated, may proceed to completion (Yang et al, 1996;Brevett et al, 2009). …”
Section: Comment On Vx Stabilitymentioning
confidence: 99%
“…In such a situation, hydrolytic degradation, once initiated, may proceed to completion (Yang et al, 1996;Brevett et al, 2009). …”
Section: Comment On Vx Stabilitymentioning
confidence: 99%
“…In addition, this information can support the choice of the decontamination technology for a specific scenario. In recent years some data was published on the desorption characteristics of the persistent CWAs O ‐ethyl S ‐2‐( N , N ‐diisopropylamino)ethyl methylphosphonothiolate) (VX) and sulfur mustard (HD) from numerous surfaces using laboratory‐sized wind tunnel devices. The results showed that bitumen‐containing surfaces, such as asphalt blocks, conserve VX and slowly release it over a long period of weeks to months .…”
Section: Introductionmentioning
confidence: 99%
“…In general, chemical reactions between and within any of the solid, liquid, or gases present in the porous media may occur. Such phenomena can contribute to the fate of droplets …”
Section: Introductionmentioning
confidence: 99%